A Long Quest for the Urban. A brief history of Ethiopian public works and the role of the outside world. - Ramos, M. (International Conference on Anthropology of Infrastructures - Barcelona, Universitat de Barcelona, 27-28 October 2016, 2016)
Ethiopia, an East African country whose economy has faced extraordinary transformations in recent years, famously underpinned by a decade of “double- digit development growth”, is today facing a situation of generalized unrest, the federal government having gone to the point of declaring a continued state of emergency, thereby extending to the whole nation a situation of direct federal militarized rule originally restricted to the Oromyia region, last November, 2015. To understand the way this shift came about, it’s useful to dig into the long history of the Abyssinian traditional state’s consolidation and expansion, and to the international relations developed before, during and after the European colonization of the African continent, and briefly elaborate both on the Christian kingdom’s long quest for “modernity” and the country’s periodic economic boosts and political revolutions (or revulsions) occasioned by international factors.